Prognostic Value of the Neutrophil to Lymphocyte Ratio (NLR) in Lung Cancer Cases - Ozyurek, Berna Akinci (Asian Pac J Cancer Prev, 2017)
Haemogram assessment is a cheap and easy method which can be readily performed for almost all patients. Leucocyte, neutrophil and lymphocyte counts and the neutrophil to lymphocyte ratio (NLR) are markers of systemic inflammation. We here aimed to evaluate haemogram parameters of our patients with lung cancer according to the pathologic diagnosis of small cell lung cancer (SCLC) and non-small cell lung cancer (NSCLC). MATERIALS AND METHODS: The study included 386 patients diagnosed with lung cancer in our hospital between January 2006 and January 2014. A retrospective examination was made of the data from the patient records and the hospital information. NLR values were categorised into two groups: <3 and ≥3. RESULTS: Median survival time in patients aged <65 years was 28.7 months and in those aged ≥65 years, it was 18.4 months (p<0.001). The median survival time was 20.2 months in NSCLC and 13.0 months in SCLC patients (p<0.001). In NSCLC cases with NLR<3 the median survival time (31.1 months) was longer than that of patients with NLR≥3 (18 months) (p=0.003). In SCLC patients, no relationship could be found between NLR and median survival time (p=0.408). With every 1 unit increase in lymphocyte count a 5.5% decrease in risk of periodic death ((1/0.947)x100=5.5%) was noted. CONCLUSION: The results of this study demonstrated that lymphocyte count, neutrophil count, Hb, Htc, and NLR are useful in determining prognosis in lung cancer (LC) patients and NLR could be more significant in determining the prognosis in NSCLC than in SCLC cases.